A short interval between bevacizumab and anti-epithelial growth factor receptor therapy interferes with efficacy of subsequent anti-EGFR therapy for refractory colorectal cancer. (12th January 2016) - Taniguchi, Hiroya; Komori, Azusa; Narita, Yukiya; Kadowaki, Shigenori; Ura, Takashi; Andoh, Masashi; Yatabe, Yasushi; Komori, Koji; Kimura, Kenichi; Kinoshita, Takashi; Muro, Kei
Abstract: Background: Both bevacizumab and anti-epithelial growth factor receptor (EGFR) agents (e.g. cetuximab and panitumumab) are sequentially used for metastatic colorectal cancer (mCRC). Their co-administration as a first-line treatment does not improve outcome, indicating that there are negative interactions between these agents. A long-term pharmacokinetics study demonstrated serum persistence of bevacizumab following termination of bevacizumab 6 months after the last administration. This prompted us to investigate the impact of short intervals between bevacizumab and anti-EGFR antibody on the efficacy of subsequent anti-EGFR therapy. Methods: We retrospectively reviewed consecutive patients with KRAS exon 2 wild-type mCRC who underwent anti-EGFR therapy after the failure of fluoropyrimidines, oxaliplatin and irinotecan. We divided patients into two groups (Group A: the interval between bevacizumab and anti-EGFR agent< 6 months; Group B: the interval >6 months). Results: Of the 114 included patients (median age, 63 years), 78 (68%) were male. Most patients (88%) were treated with cetuximab plus irinotecan. Groups A and B consisted of 74 and 40 patients, respectively. There were no significant differences in patient characteristics. Group B patients had significantly longer progression-free survival (4.2 vs. 6.6 months; HR, 0.65; 95% CI, 0.43–0.98; P = 0.038) and longer overall survival (11.6 vs. 14.3 months; HR, 0.63; 95% CI, 0.41–0.98, P = 0.039). The response rate was 24.3% in Group A and 47.5% in Group B ( P = 0.012). Conclusion: A short interval between bevacizumab and anti-EGFR antibody treatment may interfere with the efficacy of subsequent anti-EGFR therapy.